« Guideposts » for Wage-Price Behavior - Higgins, George (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1962)
SummaryThe Annual Report of the Council of Economic Advisors, which President Kennedy submitted to the Congress on January 20 is required reading for anyone who wants to keep abreast of current economic developments in the United States.The Council starts from the premise that since wage and price decisions in many crucial segments of our economy directly or indirectly affect the progress of the whole economy, « there is legitimate reason for public interest in their content and consequences. »